Morphological, ultrastructural, and molecular analysis of a new species of Myxobolus (Cnidaria, Myxosporea) parasitizing Apareiodon piracicabae (Characiformes, Parodontidae) from Brazil - Zago, Aline Cristina [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Franceschini, Lidiane [UNESP]; da Silva, Reinaldo José [UNESP] (Elsevier, 2022)
About forty-two species of Myxobolus have been previously described to parasitize characiform fishes in South America. Here, we described a new myxozoan species, Myxobolus parodontidis n. sp., in the gills of Apareiodon piracicabae (Characiformes, Parodontidae) from the streams of the Middle Paranapanema River basin, Brazil. The proposed new species is supported by a combination of morphological, ultrastructural, and molecular characterization (small subunit ribosomal DNA). Thirteen specimens of A. piracicabae were analyzed and 30.8% was infected by Myxobolus parodontidis n. sp. The myxospores was classified as intralamellar asymmetric type. A few aberrant myxospores with three polar capsules were observed: the spore length and width were the same of normal myxospores, but the polar capsules had smaller sizes. Ultrastructural analysis showed that the plasmodial membrane of Myxobolus parodontidis n. sp. was in direct contact with the host tissue and a connective capsule surrounding the plasmodium was not observed. The phylogenetic analysis showed that the main influence in the clustering of species of myxobolids seems to be related to the phylogenetic relationships established among fish hosts, mainly at the level of family and order. This is the first record of a myxozoan species parasitizing parodontid fish, contributing to the knowledge of the biodiversity of myxozoans from Brazil.
Keywords: Aberrant spores; Cnidaria parasite; Myxobolus parodontidis n. sp.; Parodontidae; ssrDNA